OUTCOME SINDROM NEFROTIK PADA ANAK – PENELITIAN PROSPEKTIF STUDI COHORT - Subandiyah, Krisni (Fakultas Kedokteran Universitas Brawijaya, 2004)
Nephrotic syndrome (NS) in children is a common recurrent disease. Most of the cases are due to minimal change disease with a favorable outcome. The mayority of children have minimal change disease and 90 – 95% will respond to steroid therapy. Response to steroid therapy carries a greater prognostic weightthan the histologic features. The aim of the studywas to describe the outcome of Nephrotic Syndrome in children and to determine risk factors for these complications. Children with NSwere admitted to Pediatric Department Saiful Anwar Hospital Malang, January 2000 - December 2003 evaluated prospectively for one year. Data was sought on steroid responsiveness, remission, relapse rates, infection, and trombosis. Patients were classified into five categories. Including: relapse, infrequent relapsing (IFRNS), frequent relapsing (FRNS), steroid dependent (SDNS) and steroidresistant (SRNS). Baseline age, gender, clinical manifestation and laboratory finding were used to predict category of the disease. Definition of NS, remission and relapse were based on the ISKDC guidelines. Of 91 children with NS, 75 (82,4%) children had steroid sensitive nephrotic syndrome (SSNS) while 16 (17,6%) children were classified SRNS. In the SSNS group 42 (56%) of children were over 6 years of age and there were 51 (68%) males and 24 (32%) females.